Solid predominant subtype in lung adenocarcinoma is related to poor prognosis after surgical resection: A systematic review and meta-analysis. Issue 7 (July 2019) - Miyahara, Naofumi; Nii, Kazuhito; Benazzo, Alberto; Hoda, Mir Alireza; Iwasaki, Akinori; Klepetko, Walter; Klikovits, Thomas; Hoetzenecker, Konrad
Abstract: Background: Recent studies have indicated that solid predominant (SP) subtype of lung adenocarcinoma (LADC) may be associated with early recurrence and worse prognosis. Hence, a systematic review and meta-analysis were performed to evaluate the association between LADC subtype and survival. Methods: The MEDLINE, SCOPUS, Web of Science and Cochrane Libraries were reviewed for eligible studies in December 2017. Studies were included if they compared outcomes of patients with and without SP subtype in resection specimens of LADC patients after surgical treatment by using multivariate Cox regression analysis. A meta-analysis for overall survival (OS) and disease-free survival (DFS) was performed. The hazard ratios (HR) or odds ratios with 95% confidence intervals (CIs) from each study were used to calculate pooled HRs. Statistical analyses were performed using Review Manager 5.3. Results: In total, 14 eligible studies including 12, 137 LADC patients were identified, which assessed the impact of SP subtype on OS and DFS in patients treated with pulmonary resection. SP subtype was reported in 1246 (10.2%) patients and was associated with significantly worse OS (pooled HR, 1.51; 1.29–1.75) and DFS (pooled HR, 1.26; 1.14–1.40). Conclusions: SP subtype is associated with significantly worse OS and DFS in patients with LADC after pulmonary resection. These data provide evidence for the integration of the distinct histological LADC subtyping into prognostic tools and guidelines for adjuvant treatment after complete surgical resection.